Optimizing collagenase Clostridium histolyticum therapy for Peyronie's disease using a novel approach with percutaneous needle tunnelling. (9th June 2019) - Fernández‐Pascual, Esaú; González‐García, Francisco Javier; Angulo, Javier; Cerezo, Eugenio; Quintana, Luis M.; Turo, Jorge; Martínez‐Ballesteros, Claudio; Carballido, Joaquín; Martínez‐Salamanca, Juan Ignacio
Abstract : Objectives: To compare the efficacy and safety of a combined treatment of percutaneous needle tunnelling (PNT) and a modified collagenase Clostridium histolyticum (CCH) protocol (PNT/CCH) vs the modified protocol alone (CCH) in the treatment of Peyronie's disease (PD). Patients and Methods: A prospective registry of patients treated with a modified CCH protocol was maintained between June 2014 and February 2018. The last 50 patients received PNT as an adjuvant therapy (PNT/CCH), and their data were compared with those of the other 94 patients treated previously (CCH). PNT involves the creation of multiple holes made percutaneously in the plaque before each injection. The modified protocol consisted of two collagenase injections, at 1‐week intervals, followed by penile modelling. Patients used penile traction therapy, tadalafil and pentoxifylline for the next 2 months and were followed up for 6 months. The main outcome was improvement of curvature. Secondary outcomes were improvements in erectile function, PD symptoms, stretched penile length and satisfaction. Results: Improvement in curvature was greater in patients in the PNT/CCH group than in the CCH group (mean ± sd 19.2 ± 6.1° vs 12.7 ± 5.0°; P < 0.001 [36.2 ± 12.5% vs 28.1 ± 14.5%; P = 0.001]). Compared with baseline, both interventions were associated with significant improvement in secondary outcomes. The main complications were ecchymosis, bruising and penile pain, with no significant differences between groups. Conclusions: Treatment of PD with CCH using our modified protocol in combination with PNT is safe and more effective than the modified protocol alone, with the potential for improved cost‐effectiveness.